Survival Benefits of Metformin for Colorectal Cancer Patients with Diabetes: A Systematic Review and Meta-Analysis - Mei, Zu-Bing (Public Library of Science, 2014)
BACKGROUND: Several studies suggest that metformin has the potential effect of reducing cancer risk. However, its survival benefit in patients with colorectal cancer (CRC) and diabetes is unknown. The aim of our study is to address the effect of metformin on outcomes for CRC based on a systematic review and meta-analysis. METHODS AND FINDINGS: We searched EMBASE and MEDLINE databases from inception through August, 2013, using search terms related to metformin, diabetes, colorectal cancer, and prognostic outcome. The outcome measures were hazard ratios (HRs) with 95% CIs comparing CRC survival in diabetic patients using metformin and without using metformin. The primary end points were overall survival (OS) and CRC specific survival (CS). A total of six cohort studies including 2,461 patients met full eligibility criteria. The pooled HR favoring metformin users was 0.56 for OS (95% CI, 0.41 to 0.77) and 0.66 for CRC-specific survival (95% CI, 0.50 to 0.87). Thus metformin therapy reduced the risk of all cause of death by 44% and the risk of CRC specific death by 34% in CRC patients compared to those in non-users. However, evidence of heterogeneity and possible publication bias was noted for OS. CONCLUSIONS: Patients with CRC and diabetes treated with metformin appear to have an improved survival outcome. Prospective study should be warranted to examine the association between metformin exposure intensity as well as some other confounding variables and survival outcome in diabetic CRC patients.